Initial Assessment of Tidal Current Energy Resource at Aroih Raya, at Aceh Waters, Indonesia using Delft3D Numerical Modelling - Miftahul Chosyi; Munawir Pratama; Farda Jamila; Revi Rosa Liana (Jurnal Teknik Sipil, 2025)
Abstract